Analisis Model Pembelajaran Pendidikan Agama Islam Dalam Meningkatkan Minat Belajar Peserta Didik Madrasah Ibtidaiyah Negeri 02 Pringsewu - inarotul ulya , Ina; wulan octi pratiwi, wulan; Diani , Eva Riantika (An Naba, 2024)
This study was conducted to determine the learning model used by educators to increase students' interest in learning. This study uses a qualitative method, educators use various student learning models such as cooperative learning models, problem-based learning models, project-based learning models, inquiry learning models, contextual learning models, and flipped learning models. These various learning models are expected to increase students' interest in learning MIN 2 Pringsewu Keywords : Learning Model, Interest in learning.